Factors that impact Australian early career nurses' intentions to remain in their position and the profession: A prospective cohort study. (7th October 2022) - Cottle‐Quinn, Amanda; Tower, Marion; Eley, Rob
Abstract: Aim: The aim of this work is to identify factors that impact on early career nurses' intentions to remain in their current position and compare with what impacts on intention to remain in the profession. Background: Early exits of nurses from a position and the profession are a result of evolving factors. A lack of longitudinal follow‐up impedes knowledge about these factors or what proportion of temporary exits become permanent. Method: The study used prospective cohort survey design. The sample was obtained from non‐probability convenience sampling of graduating nursing students from two universities. Data was collected across three time points over 12 months, commencing in November 2016. Results: The professional turnover rate was 6.7% in total. Higher Work Environment, Support and Encouragement scores and Stress in personal life were the only predictors of intending to remain in the profession. Statistical modelling could not predict intention to remain in current position. Conclusion: There were differences identified when comparing intention to remain in a position and the profession. Nurses are satisfied with their career choice and intend to remain in the profession, although many are intending to move positions. Implications for Nursing Management: To effectively retain the nursing workforce, stakeholders must focus on the work environment, appropriate support and remuneration, and facilitate career progression.